Postmodernizem in zgodovinskost v srbski književnosti - Tomazin, Tanja (Primerjalna književnost, 2015)
The contribution discusses the ways in which Serbian postmodernism expresses a relatively high degree of engagement within the national literary system precisely through a thematization of the historical, an engagement that occurs on two levels: the poetics of narration itself and the intellectual stance of postmodernist writers. While the first line of engagement entails the construction of various apocryphal histories working to reveal the interrelation of narrative and a unified representation of the past in the service of the political elite, the second manifests itself as a conscious refusal to address current social and political issues at the expense of the so-called postmodernist hedonism. In view of the nature of its poetics, the engagement of postmodernism is paradoxical, and in the context of the system perhaps nothing short of revolutionary.
Keywords: družbenopolitični angažma; historiografska metafikcija; književnost in zgodovina; literarni sistem; postmodernizem; roman; srbska književnost